Pengembangan Model Pembelajaran Nahwu Aplikatif Berbasis Project-Based Learning untuk Meningkatkan Pemahaman Kaidah dan Aplikasinya - Anwar Sidik; Hidayah, Nur Hidayah (PT. Intelek Cendikiawan Nusantara, 2025)
The present study aims to develop an applied Nahwu learning model based on project-based learning that can enhance students’ understanding of Nahwu rules and their ability to apply them when analyzing the structure of Arabic sentences. The background of this research stems from the low ability of students to apply Nahwu rules contextually, despite having studied the theory intensively. This study employs a Research and Development (R&D) method using the Borg and Gall development model, which includes the stages of needs analysis, model design, expert validation, limited trials, and revision. The research subjects consisted of third-semester students of the Arabic Language Education Study Program at the Institute of Qur’anic Science Syekh Ibrahim. Data were collected through observation, questionnaires, interviews, and learning outcome tests. The findings indicate that the project-based Nahwu Tathbiqiy learning model is valid and practical based on evaluations by language experts and learning specialists, with a feasibility percentage of 89%. The implementation of this model successfully increased students’ active engagement in the learning process through project activities such as text analysis, sentence construction, and presentation of analysis results. The effectiveness test further shows a significant improvement in students’ understanding of Nahwu rules and their application in sentence contexts after the model’s implementation. Therefore, the project-based Nahwu Tathbiqiy learning model is deemed suitable as an innovative alternative in Arabic language instruction, balancing conceptual understanding and practical application skills.